Effects of Al-dopant at Ni or Co sites in LiNi0.6Co0.3Ti0.1O2 on interlayer slabs (Li–O) and intralayer slabs (TM–O) and their influence on the electrochemical performance of cathode materials. Issue 66 (5th November 2020) - Wan Azizan, Wan Aida Hazwani; Kasim, Muhd Firdaus; Elong, Kelimah; Rusdi, Roshidah; Mohd Rosnan, Rizuan; Kamarulzaman, Norlida
Abstract : Al substitute into Ni site increase Li–O and reduce M–O atomic distance lead to excellent cycleability with high energy density. Abstract : In order to satisfy the energy demands of the electromobility market, further improvements in cathode materials are receiving much attention, especially high energy density cathode materials for Li-ion batteries (LIBs). In this work, the self-propagating combustion (SPC) method is use to synthesise undoped LiNi0.6 Co0.3 Ti0.1 O2 (LNCT), novel nano-sized Al-doped LiNi0.6 Co0.3− x Al x Ti0.1 O2 (LCA) and LiNi0.6− x Co0.3 Al x Ti0.1 O2 (LNA) ( x = 0.01) cathode materials. LNCT, LCA and LNA were annealed at 700 °C for 24 h. Following the synthesis, the phase, chemical structure and purity of the materials were analysed using X-ray diffraction (XRD). Based on the XRD results, all materials exhibit a single-phase structure with rhombohedral layered structure. Based on the HRTEM and EDX results, all samples exhibit polyhedral-like shapes, while the Al-doped samples display smaller crystallite sizes compared to the undoped sample. As for the electrochemical performances, the initially discharged capacity of LCA (238.6 mA h g −1 ) is higher than that of LNA (214.7 mA h g −1 ) and LNCT (150.5 mA h g −1 ). However, LNA has a lower loss of capacity after the 50 th cycle compared to the LCA sample, which makes it a more excellent candidate for electrochemical applications. The main reason for the excellent electrochemical behaviour of LNA is due to lower cation mixing. Furthermore, Rietveld refinements reveal that the LNA sample has a longer atomic distance of Li–O and shorter TM–O in the cathode structure, which makes Li + ion diffusion more efficient, leading to excellent electrochemical performance. These findings further proved the potential of the novel nano cathode material of LiNi0.6− x Co0.3 Al x Ti0.1 O2 (LNA) to replace the existing commercialized cathode materials for rechargeable Li-ion batteries.